URBAN GEOSITES AND RECREATIONAL TOURISM. BAHÍA BLANCA, ARGENTINA - Jorgelina Leguizamón; Verónica Gil; Valeria Natalia Gil (Boletín Geográfico)
This work uses the term geosites in order to evaluate the potential of geodiversity for the tourist use through geotourism. In Argentina, the initiatives of this new tourist modality are scarce comparing with other countries of greater visibility and insertion in the market. Therefore, the aim of this work is to characterize two geosites for their evaluation as tourist-recreational spaces in the city of Bahía Blanca. These geosites reflect the geological history of the last 10 M.a. in the area. In this way, the purpose is to capitalize new urban and peri-urban spaces within the most current modalities of the tourism market. In this case, the use of tourist trails with interpretive signage in situ would allow outdoor activities and develop a better involvement with the territory, raising awareness among the population for their care and preservation for future generations.